The dangers of new media technology and the challenges of family - Houria, BENHAMZA (Journal of Humanities & Social Sciences, 2022)
Modern technology and new media, that are used in the process of communication between individuals and groups, have become widely popular for various purposes including recreational, cultural, and educational, which led to changes in social structures and in the intellectual, behavioral and cultural patterns of individuals, and had negative effects on Family privacy and functions, which weakened the importance of family upbringing and the family’s educational role. In this research paper, we will present the most important social problems facing the family within the process of upbringing in light of the widespread users of social networking sites, especially as a result of Internet addiction among children and youth.